Prejudice at the nexus of race and gender an outgroup male target hypothesis. [article]. - Navarrete, Carlos David
Adopting an evolutionary approach to the psychology of race bias, we posit that intergroup conflict perpetrated by male aggressors throughout human evolutionary history has shaped the psychology of modern forms of intergroup bias and that this psychology reflects the unique adaptive problems that differ between men and women in coping with male aggressors from groups other than one's own. Here we reports results across 4 studies consistent with this perspective , showing that race bias is moderated by gender differences in traits relevant to threat responses that differ in their adaptive utility between the sexes-namely, aggression and dominance motives for men and fear of sexual coercion for women. These results are consistent with the notion that the psychology of intergroup bias is generated by different psychological systems for men and women, and the results underscore the importance of considering the gender of the outgroup target as well as the gender of the agent in psychological studies on prejudice and discrimination.
Keywords: Ingroup bias; Evolutionary psychology; Prejudice; Sex differences; Social dominance